Label‐free quantification of the effects of lithium niobate polarization on cell adhesion via holographic microscopy. Issue 8 (18th April 2018) - Mandracchia, Biagio; Gennari, Oriella; Bramanti, Alessia; Grilli, Simonetta; Ferraro, Pietro
Abstract : The surface of a c− cut ferroelectric crystal at room temperature is characterized by the so‐called screening surface charges, able to compensate the charge due to the spontaneous polarization. Recently, these charges inspired the investigation of the interaction affinity of live cells with lithium niobate and lithium tantalate crystals. However, different knowledge gaps still remain that prevent a reasonable application of these materials for biological applications. Here, a label‐free holographic total internal reflection microscopy is shown; the technique is able to evaluate quantitatively the contact area of live fibroblast cells adhering onto the surface of a ferroelectric lithium niobate crystal. The results show values of contact area significantly different between cells adhering onto the positive or negative face of the crystal. This reinforces the reasons for using the polarization charge of these materials to study and/or control cellular processes and, thus, to develop an innovative platform based on polar dielectric functional substrates. Abstract : The surface of a c− cut ferroelectric crystal at room temperature is characterized by screening surface charges, able to compensate the charge due to the spontaneous polarization. Here, we use holographic TIR microscopy show that cell adhesion is significantly different between the positive and negative face of a crystal of lithium niobate.